Density weighted turbo spin echo imaging. Issue 4 (16th January 2013) - Zeller, Mario; Gutberlet, Marcel; Stäb, Daniel; Ritter, Christian Oliver; Beer, Meinrad; Hahn, Dietbert; Köstler, Herbert
Abstract Purpose To optimize the spatial response function (SRF) while maintaining optimal signal to noise ratio (SNR) in T2 weighted turbo spin echo (TSE) imaging by prospective density weighting. Materials and Methods Density weighting optimizes the SRF by sampling the k‐space with variable density without the need of retrospective filtering, which would typically result in nonoptimal SNR. For TSE, the T2 decay needs to be considered when calculating an optimized sampling pattern. Simulations were carried out and T2 weighted in vivo TSE measurements were performed on a 3 Tesla MRI system. To evaluate the SNR, reversed centric density weighted and retrospectively filtered Cartesian acquisitions with identical measurement parameters and SRFs were compared with TEeff = 90 ms and a density weighted k‐space sampling optimized to yield a Kaiser function for SRF side lobe suppression for white matter. Results Density weighting of a reversed centric reordering scheme resulted in an SNR increase of (43 ± 13)% compared with the Cartesian acquisition with retrospective filtering while maintaining comparable contrast behavior. Conclusion Density weighting is applicable to TSE imaging and results in significantly increased SNR. The gain can be used to shorten the measurement time, which suggests applying density weighting in both time and SNR constrained MRI. J. Magn. Reson. Imaging 2013;37:965–973. © 2013 Wiley Periodicals, Inc.